Research of the Influence of Helicopter Power Transmission System on Rotor Shimmy Modal and Experimental Verification - Lai Lingyun; Zhang Ruochen; Liu Yongzhi (Jixie chuandong)
The torsional vibration dynamics analytical model of rotor power transmission system is built,the shimmy collectivity mode of vibration and frequency of rotor blade are obtained,it is indicated that the propulsion/transmission system will influence shimmy mode obviously, the frequency of blade shimmy will be changed. Through the torsional vibration frequency test of helicopter rotor power transmission system,method and result correctness are verified.